RANCANG BANGUN PROGRAM APLIKASI QUIZ BAHASA INGGRIS MENGGUNAKAN MICROSOFT VISUAL BASIC 6.0 - Sukmono Bayu Adhi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
The purpose of this study is to find out the process of utilizing and software making that can be used to evaluate students in learning English. By utilizing the advances in computer technology (artificial intelligence), it is expected that this application program can help tutors, teachers, and lecturers in providing evaluations of English course (English quizzes) to their students more efficiently. The advantage of using this application is that, for students the process of evaluating or quiz becomes more fun and practical because it is done directly on a computer or laptop without the need for paper and other stationery. The second advantage is that the quiz assessment process will be carried out directly by using the computer so that it can be more efficient for the instructors. By this program they do not need to manually correct it because the final score or result will appear automatically after all the questions have been completed by students. This application program is created using the Visual Basic 6.0 programming language.